2013
DOI: 10.1016/j.jcin.2013.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Renal Function–Based Contrast Dosing Predicts Acute Kidney Injury Following Transcatheter Aortic Valve Implantation

Abstract: Although mechanisms of AKI following TAVI are multifactorial, the present study identified a relationship between CM dose increment and high prevalence of AKI. Therapeutic efforts not to exceed the threshold value may reduce the risk of AKI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
108
1
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(119 citation statements)
references
References 33 publications
8
108
1
2
Order By: Relevance
“…Nevertheless, several previous investigations have identified that a ratio of contrast media  serum creatinine/body weight over 2.7 is associated with an increased risk of AKI after TAVI; therefore, the contrast dose should be adjusted [16].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, several previous investigations have identified that a ratio of contrast media  serum creatinine/body weight over 2.7 is associated with an increased risk of AKI after TAVI; therefore, the contrast dose should be adjusted [16].…”
Section: Discussionmentioning
confidence: 99%
“…110 In coronary interventions, a contrast volume >100cc has been associated with AKI. 111 Only one study has demonstrated a linear relationship between the ratio of contrast to body size and subsequent AKI in TAVR 92 .…”
Section: Association Of Aki With Mortality Morbidity and Long-term mentioning
confidence: 99%
“…In previous studies, when patients that developed AKI were compared to those that didn't the 30-day and 1-year mortality was significantly higher in those with AKI. 90,[92][93][94][96][97][98][99][100] Patients requiring renal replacement therapy (RRT) after TAVR had on average a 3-fold increase in 30-day mortality and a 3.3-fold increase in 1-year mortality as compared with patients with AKI of lower severity. In a recent meta-analysis of randomized controlled trials in TAVR, there was no association between TAVR and reduced risks of short term mortality (<1 year, RR 0.84, 95% CI 0.56-1.26); 102 patients that developed AKI following TAVR stayed 1.5 to 2 fold longer in hospital than patients without AKI.…”
Section: Association Of Aki With Mortality Morbidity and Long-term Rmentioning
confidence: 99%
“…However, these variables do not differ among the groups in our study (tables 1, 2). With regard to surgery, factors that facilitate CIN development are: increase in the amount of contrast medium, hemodynamic irregularities, and hypotension [12,13,14,15,16,17,18,19,20,21]. During TAVI operation in particular, hypotensive periods may occur, thus increasing CIN probability.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, factors that can lead to the development of CIN after interventional cardiovascular operations must be well known. It has been specified that the contrast medium volume (CV) used in invasive operations is the most important factor causing AKI [12,13]. The CV/glomerular filtration rate (GFR) ratio, a useful indicator of the development of nephropathy, depends on the amount of contrast medium administered after percutaneous coronary intervention (PCI) [14].…”
Section: Introductionmentioning
confidence: 99%